Board of directors and capital structure: evidence from leading Malaysian companies - Teh, Boon Heng; Azrbaijani, Shabnam; Ong, Tze San (Canadian Center of Science and Education, 2012)
Malaysia is one of the rapidly developing economies in South-East Asia which embraces the concept of good corporate governance due to the 1997-1998 Asian financial crises. This study investigates the relationship between board of directors and company’s capital structure in an emerging market, Malaysia. This research paper covers 75 non-financial leading Malaysian companies, which are employed as a price index, listed on Kuala Lumpur stock exchange (KLSE) from the year 2005 to 2008 fiscal years. A multiple regression analysis has been used to examine the linkage between board of director’s features and capital structure decisions of the listed companies. Measures of board of directors employed are size of the board, presence of non-executive directors on the board, presence of independent non-executive directors on the board and CEO/Chair duality. Results reveal that board size and presence of independent non-executive directors on the board have significant, negatively and positively correlation with debt to asset ratio respectively. However corporate capital structure decisions are not found significantly influenced by CEO/Chair duality and the presence of non-executive directors on the board. Consequently based on the results, board of director’s features such as board size and presence of independent non-executive directors on the board play an important role in determination of financial mix of the companies.